Mislabeling latent variables in factor analysis applied to football playing style research: A commentary - Spyridon Plakias (Physical Education and Sports: Studies and Research, 2026)
The application of exploratory factor analysis and principal component analysis (PCA) has become increasingly prevalent in football analytics, offering a robust framework for identifying and quantifying playing styles. By condensing a large set of performance indicators into factors, these techniques provide valuable insights into tactical patterns. However, a persistent challenge lies in the subjective labeling of these factors, which can lead to ambiguous or misleading interpretations. This commentary highlights the issue of mislabeling latent variables in football playing style research, drawing on examples from recent studies to illustrate how inaccurate labels can distort both theoretical understanding and practical applications. The implications of poor labeling extend beyond academic discourse, potentially affecting coaches and analysts who rely on data-driven insights for tactical planning. To address these challenges, we propose best practice recommendations emphasizing conceptual clarity, standardized terminology, and expert validation. Accurate and consistent factor labeling is essential to ensure the reliability, comparability, and practical relevance of findings in the evolving field of football performance analysis.